A new species of Calyptotheca (Bryozoa: Cheilostomata) from Alexandria, Egypt, southeastern Mediterranean - Abdelsalam, Khaled M.; Taylor, Paul D.; Dorgham, Mohamed M. (Zootaxa, 2017)
Beginning in December 2015, an unknown bryozoan with large, deep-orange colonies began to appear in the Eastern Harbour of Alexandria, Egypt. Here we identify the species as belonging to the predominantly Indo-Pacific cheilostome genus Calyptotheca Harmer, 1957 and describe it as a new species, Calyptotheca alexandriensis n. sp. The new species exhibits intensive growth sporadically on different hard substrata, including rocks, submerged concrete walls, ropes, ships’ hulls, and metal pipes supporting marina piers. It is restricted to the Eastern Harbour, particularly in shallow parts, with the densest aggregations on the metal pier supports. The source of this bryozoan is enigmatic but most likely involved introduction by shipping.